1998
DOI: 10.1111/1468-2389.00093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Centre Observation Procedures: An Experimental Comparison of Traditional, Checklist and Coding Methods

Abstract: Concern about the construct validity of assessment centre judgements has led to calls for research into observers' cognitive processes. In an experiment comparing the Traditional observation procedure against use of a Behavioural Checklist and of Behavioural Coding, six outcome variables were examined. The methods were found to yield similar outcomes in terms of accuracy of judgement, accuracy of written evidence, correlation between dimension ratings, and attitude toward the method employed. However, signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
11
1
1
Order By: Relevance
“…Although the present results and the results by Hennessey et al (1998) do not support that taking notes increases the quality of the ratings, it cannot be uniformly concluded that assessors might as well skip taking notes during the exercise. The Guidelines (Task Force on Assessment Center Guidelines 1989) specifically state that a systematic procedure must be used by assessors to record accurately specific behavioural observations at the time of their occurrence.…”
Section: Study Implicationscontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the present results and the results by Hennessey et al (1998) do not support that taking notes increases the quality of the ratings, it cannot be uniformly concluded that assessors might as well skip taking notes during the exercise. The Guidelines (Task Force on Assessment Center Guidelines 1989) specifically state that a systematic procedure must be used by assessors to record accurately specific behavioural observations at the time of their occurrence.…”
Section: Study Implicationscontrasting
confidence: 99%
“…However, results showed no significant differences between observation methods or types of assessors. This result is similar to Hennessey et al (1998) who also failed to find decreased inter-dimension correlation when they compared the traditional observation method with the behavioural checklists and coding method (this latter method involved tallying behaviours during the exercise on a behavioural checklist, rather than recording them). Yet, it is important to realize that both this study and the Hennessey et al study applied a design divergent from the regular candidate  dimension designs to study halo, because this design examines the ratings of multiple assessors and only a few candidates.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Reilly et al (1990) showed that the use of behavioral checklists or realistic behavioral descriptions improved construct validity because the assessors were able to relate assessee behavior more clearly to the various dimensions of job requirements. Hennessy, Mabey, and Warr (1998) experimentally demonstrated the superiority of behavioral checklists and behavioral coding over traditional observational systems. Behavioral observation scales usually only use key words to express the job requirements, which are not clearly enough delineated to begin with.…”
Section: Use Of Multiple Techniques Suited For Observingmentioning
confidence: 99%